Securing Prosperity : The American Labor Market: How It Has Changed and What to Do about It - Osterman, Paul (Book collections on Project MUSE., 2001)
We live in an age of economic paradox. The dynamism of America's economy is astounding--the country's industries are the most productive in the world and spin off new products and ideas at a bewildering pace. Yet Americans feel deeply uneasy about their economic future. The reason, Paul Osterman explains, is that our recent prosperity is built on the ruins of the once reassuring postwar labor market. Workers can no longer expect stable, full-time jobs and steadily rising incomes. Instead, they face stagnant wages, layoffs, rising inequality, and the increased likelihood of merely temporary wor.